Tau-Path Following Method for Solving the Riccati Equation with Fractional Order. (5th March 2014) - Syam, Muhammed I.; Siyyam, Hani I.; Al-Subaihi, Ibrahim
Abstract : A formulation for the fractional Legendre functions is constructed to find the solution of the fractional Riccati equation. The fractional derivative is described in the Caputo sense. The method is based on the Tau Legendre and path following methods. Theoretical and numerical results are presented. Analysis for the presented method is given.